Improving Sustainability of Rice-Wheat system through intensification - Tripathi, S C; Chander, Subhash; Meena, Raj Pal (Indian Farming, 2017)
Maximum equivalent wheat yield (15.21 t/ha), production efficiency (46.81 kg/ ha/ day), land use efficiency (89.04 %), total return (`1, 82,551/ha), net return (` 49, 351/ha) and B: C ratio (1.37) were recorded in rice-wheat -green gram cropping sequence where latter two crops, i.e. wheat and green gram were grown under bed planting system. In contrast, these parameters were the lowest in rice-wheat system. This suggested that all the intensifications options are more profitable as compared to rice-wheat system. Therefore, farmers are advised to grow pulses for intensification of rice-wheat system. Among the selection of three pulses, maximum profit was with green gram followed by cowpea and vegetable pea. Growing summer green gram or cowpea could also avoid in pumping of water with additional benefits like increasing pulse production and saving of about 25 % nitrogen requirement to succeeding rice crop.